Effect of Different Particle Sizes on The Akara Making Potentials of Pigeon Pea Flour - Linus-Chibuezeh, Adindu; Okoye-Okeke, Chinenye; Adindu-Linus, Chidiamara; Iwe, Maduebibisi Ofo (Department of Technology of Agricultural product (THP) Jambi University, 2021)
The study evaluated the potentials of Pigeon pea (Cajanus cajan) flour in the production of akara (fried cake). The flour samples were produced by soaking the seeds in water, dehulled, oven dried and ground to flour and divided into 4 units. The flour was passed through sieve of different size while the control was not sieved. Physicochemical and sensory analyses were conducted for the flour and akara using standard methods and results were presented as mean Â± standard deviation using ANOVA. Significance was accepted for pâ‰¤0.05 by Duncan multiple range test. Result of functional properties showed that the sieved pigeon pea bulk density, emulsion capacity and foam capacity increased with increase sieve aperture in the range 0.73 to 0.81(g/mg), 43.08 to 46.66, and 44.35 to 46.14 respectively, while wettability (1.53 to 1.88) and gelation capacity (11.10 to 11.17) decreased. The results of the proximate composition of the akara showed values for pigeon pea and cowpea flours in moisture content, ash, fibre, protein and carbohydrates. The Sensory evaluation results showed that all the sensory parameters evaluated increased with decreased sieve aperture and differed significantly with respect to overall acceptability. Keywords: proximate, sensory, quality, cowpea